Management of Al-Qur’an Learning in Early Children - Ratu Noor Khalidah; Ahmad Suriansyah; Aslamiah Aslamiah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Management of Al-Qur'an learning in early childhood can create quality Al-Qur'an learning. This study aims to analyze the management of Al-Qur’an learning. Multisite descriptive qualitative research approach at PAUD Qur’an Cahaya Ar-Raudah and PAUD Terpadu Shabwa Amanah. Collection of interview data, observation and documentation. Data analysis: (1) Individual data (2) Cross-site data. Research results: 1) Planning is prepared by the PAUD head together with the teacher with a new school year meeting by compiling a Al-Qur'an learning program followed by setting goals, targets, methods, materials, media, assessment and Al-Qur'an learning time 60 minutes 2) The implementation uses the tilawati method, consisting of initial activities, core activities: classical learning and individual learning, finally closing activities. 3) The evaluation assesses the Al-Qur'an recitation test and the short surah memorization test. Daily assessments use achievement books, star stamps and checklist sheets and semester assessments use munaqosyah assessment report cards and child development reports.